Development of innovative motifs from existing adinkra symbols for ’ahenema’ footwear - Frimpong, Charles Amoah (2016)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of the degree of Master of Philosophy in Integrated Art (Leather Technology), 2015